(untitled) (Biological Sciences - PJSIR, 2024)
Fruits and vegetable’s peels which are usually discarded during consumption and processing and good source of nutrients. Pumpkin is extensively grown and consumed vegetable in subcontinent. Pumpkin peel is considered as waste material and discarded, which contains essential nutrients in sufficient quantities. In present study pumpkin peel powder (PPP) biscuits were developed by the replacement of straight grade flour (SGF) of wheat, with 0, 5, 10 and 15% of PPP and standardized. Physico-chemical analyses of PPP, SGF and developed biscuits which were performed. Ash, fat and fibre contents were higher in PPP as compared to SGF whereas, moisture and protein contents were lesser. By increasing the replacement level of PPP with SGF, a significant increase in ash, fat and fibre in biscuits was observed, whereas, moisture and protein contents were slightly decreased. Colour analysis of SGF and PPP revealed that a* (redness) and b* (yellowness) values of PPP were higher than SGF, whereas, L* (lightness) values of PPP were less than SGF. By increasing replacement level of PPP with SGF, a* and b* values significantly increased. Mineral analysis revealed that Na, K and Fe were higher in PPP and increased in biscuits by increasing the level of PPP, whereas Ca, Mg and P were lesser in PPP as compared to SGF. Upon sensory evaluation, biscuits developed with 5% level of PPP, got highest scores, close to the control, whereas 15% level was not liked by the judges. Biscuits incorporated with pumpkin peel powder could be a good choice in market as functional food products demanded by health-oriented consumers.